The Future of Economic Theory - Clark, John Bates (Quarterly Journal of Economics, 1898)
The Future of Economic Theory John Bates Clark John Bates Clark Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 1, October 1898, Pages 1–14, https://doi.org/10.2307/1882980 Published: 01 October 1898